Best-bet integrated strategies for containing drug-resistant trypanosomes in cattle - Mungube Erick O; Diall Oumar; Baumann Maximilian PO; Hoppenheit Antje; Hinney Barbara; Bauer Burkhard; Sanogo Yousouf; Maiga Brehima; Zessin Karl-Hans; Randolph Thomas F; Clausen Peter-Henning (Parasites & Vectors, 2012)
Abstract Background African animal trypanosomosis is a major constraint to the rearing of productive livestock in the sub-humid Sudan-Sahel zone of West Africa where cotton is grown. Trypanosomosis is mainly controlled using trypanocidal drugs, but the effective use of drugs is threatened by the development of widespread resistance. This study tested integrated best-bet strategies for containment and/ or reversal of trypanocide resistance in villages in south-east Mali where resistance has been reported. Methods Four sentinel villages each from an intervention area (along the road from Mali to Burkina Faso) and a control area (along the road from Mali to Côte d’Ivoire) were selected for the study. Tsetse control was based on deltamethrin-treated stationary attractive devices and targeted cattle spraying between March 2008 and November 2009. Trypanosome-positive cattle were selectively treated with 3.5 mg/kg diminazene aceturate. Strategic helminth control using 10 mg/kg albendazole was also undertaken. During the intervention, tsetse densities along drainage lines, trypanosome infections and faecal egg counts in risk cattle (3 to 12 months of age) were monitored. Results Catch reductions of 66.5 % in Glossina palpalis gambiensis and 90 % in G. tachinoides were observed in the intervention area. Trypanosome prevalence was significantly (p < 0.05) lower in the intervention area (2.3 %; 1.3-3.6 %) compared to the control area (17.3 %; 14.8-20.1 %). Albendazole treatment resulted in a faecal egg count reduction of 55.6 % and reduced trypanosome infection risk (2.9 times lower than in the placebo group) although not significantly (p > 0.05). Further studies are required before confirming the existence of albendazole resistant strongyles in the study area. Conclusion Integration of best-bet strategies in areas of multiple drug-resistance is expected to reduce trypanosome infection risk thus contributing to containment of trypanocidal drug resistance. Integrated best-bet strategies could therefore be considered a viable trypanosomosis control option especially in areas where multiple drug-resistance has been reported.